2002
DOI: 10.1504/ijram.2002.002553
|View full text |Cite
|
Sign up to set email alerts
|

Enacting risk in independent technological innovation

Abstract: Abstract:The present study aims at investigating the role of risk in the activity of independent technological venturing. Altogether 12 deep-interviews were conducted with technological entrepreneurs, who had taken part in the inventive, developmental and the commercialisation phases of a technologybased innovation process. The interviews revealed a number of enactment approaches through which these innovators encountered and affected (dealt with or transformed) risk within the innovation process. Factors thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…Already, phenomenological investigations of entrepreneurial risk taking (e.g. Berglund and Hellström, 2002) and failure (e.g. Cope, 2011) suggest that understanding how entrepreneurs take risk and learn from failure must include issues of a highly personal, emotional and social character.…”
Section: Discussionmentioning
confidence: 99%
“…Already, phenomenological investigations of entrepreneurial risk taking (e.g. Berglund and Hellström, 2002) and failure (e.g. Cope, 2011) suggest that understanding how entrepreneurs take risk and learn from failure must include issues of a highly personal, emotional and social character.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent project (Berglund and Hellström 2002), a phenomenological method was used to investigate risk among a number of high-tech entrepreneurs in Sweden. This study sought to elucidate the variety of ways in which risk is experienced and enacted by entrepreneurial high-tech innovators as they develop their ventures, and the example illustrates how phenomenological methodology may be used in terms of sampling, data collection, analysis and how the results can be written up and presented.…”
Section: A Worked Example Of Phenomenological Methodologymentioning
confidence: 99%
“…The ambition was to increase understanding of how entrepreneurs perceive and deal with the phenomenon of risk in the course of developing their ventures, but also to explore specific strategies that may be employed by practitioners and used by researchers for further theorizing. In the original paper we used the results to discuss and elaborate on previous research on entrepreneurship and risk (see Berglund and Hellström 2002), but as suggested by Giorgi and van Manen, phenomenological results can be used in many different ways. The next section touches more generally on the potential advantages and drawbacks of a phenomenological approach.…”
Section: Summary Of Methodological Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example lies in the complex proprietary/non-contractual arrangements that develop between firms and universities in biotechnology, where hybrid entrepreneurs merge industry with university networks. Typically, 'gift-giving' practices develop -where, for instance, a researcher uses the expensive equipment of the new biotech company, in return for which s/he gives knowledge and expertise (Berglund and Hellström, 2002).…”
Section: Externalmentioning
confidence: 99%